2015
DOI: 10.1007/s00402-015-2306-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma did not improve early healing of medial collateral ligament in rats

Abstract: The addition of PRP to a healing MCL did not improve any of the outcome measures in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The 31 in vivo ligament studies used various ligament models, including rat MCL, 2 canine ACL, 5,13,48,49,54,58,62,63 porcine ACL, 3,22,23,27,29,39,45 47 rabbit MCL, 14,26,31,40,66 rabbit ACL/CCL, 1,32,52,59,67 and human ACL (Appendix Table A3). 50,55,60 Among in vivo studies, detection and performance biases were consistently high, whereas selection, attrition, reporting, and other biases were consistently low (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 31 in vivo ligament studies used various ligament models, including rat MCL, 2 canine ACL, 5,13,48,49,54,58,62,63 porcine ACL, 3,22,23,27,29,39,45 47 rabbit MCL, 14,26,31,40,66 rabbit ACL/CCL, 1,32,52,59,67 and human ACL (Appendix Table A3). 50,55,60 Among in vivo studies, detection and performance biases were consistently high, whereas selection, attrition, reporting, and other biases were consistently low (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“… a References 1, 2, 3, 10, 11, 13, 14, 22, 23, 26, 27, 29, 30, 31, 36, 39, 41, 50, 51, 52, 56, 57, 63, 64, 65, 66. …”
mentioning
confidence: 99%
“…Many recent papers have reported that PRP is of benefit in the treatment of chronic tendon injuries, and many experimental studies have evaluated the effect of PRP on healing of MCL injury in animal models. [9][10][11] Yoshioka et al 9 evaluated the effect of PRP on MCL healing in a rabbit model and found that PRP treatment promoted healing of the MCL. In a rat model of MCL injury, Amar et al 10 found no evidence to support a benefit of PRP for MCL healing in the acute stage.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Yoshioka et al 9 evaluated the effect of PRP on MCL healing in a rabbit model and found that PRP treatment promoted healing of the MCL. In a rat model of MCL injury, Amar et al 10 found no evidence to support a benefit of PRP for MCL healing in the acute stage. LaPrade et al 11 found that high doses of PRP decreased the quality of repair tissue in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…A traumatic injury is followed by the formation of a platelet-rich hematoma, which releases growth factors and cytokines, which in turn stimulate the healing process 25 . Kajikawa et al 26 .applied PRP to rat patellar tendon and found an increase in the number of blood cells using labeled proteins.…”
mentioning
confidence: 99%